Expandindo o uso do teste de caminhada de seis minutos em pacientes com doença arterial periférica sintomática e avaliando suas relações com a capacidade funcional e função cardiovascular - Sant´Anna, Fernando da Silva (2021)
The six-minute walk test (6MWT) has been widely used in patients with symptomatic peripheral arterial disease (PAD) to quantify disease severity, gait impairment and the effectiveness of different therapeutic interventions. However, the information provided by this test can go beyond the meters covered. The aim of this thesis was to expand the use of the 6MWT in patients with PAD, describing their relative values compared to peers without the disease and using the product of distance by body weight (DW) as a new way to interpretation 6MWT data. Furthermore, the second objective was to analyze the relationship of new interpretations with functional capacity and cardiovascular variables. Therefore, 227 patients with symptomatic PAD participated in the study. The 6MWT was performed and the onset claudication distance and the total walking distance in six minutes were obtained. The results of the 6MWT were then relativized and expressed as a percentage of a healthy individual without PAD. Additionally, from the obtained absolute distance, the DW was calculated. Functional capacity was objectively assessed using the Short Physical Performance Battery and the handgrip strength test, and subjectively using questionnaires (Walking Impairment Questionnaire and Walking Estimated-Limitation Calculated by History). The indicators of the cardiovascular system were obtained by measuring brachial blood pressure (BP), central blood pressure and arterial stiffness indicators (pulse pressure, augmentation index itself and corrected by 75 bpm, and pulse wave velocity). The results of the 6MWT were compared between genders using the independent t test. To analyze the influence of different age categories (≤59 years, 60-69 years and ≥70 years), one-way ANOVA was applied. To test the relationship between the variables, Spearman's correlation was performed. Values with P<0.05 were considered significant. As a result, it was possible to observe in both sexes that the relative distance of the 6MWT ranged from 57% to 64%. Stratified by age groups, the total and relative 6MWT distance was similar between age categories (P>0.072). The DW was higher in men than in women (P<0.050). Furthermore, in women, the DW was higher in the younger group compared to other age groups (P<0.050). The relative 6MWT distance and the DW were correlated with all functional capacity variables (P<0.001). When stratified by sex, there was no correlation of subjective variables in men. Relative 6MWT and DW in women were correlated with ABI (P=0.009 and P=0.004, respectively), central systolic BP (P=0.050 and P=0.003, respectively) and indicators of arterial stiffness (P<0.008). It was possible to conclude that relativized 6MWT values demonstrate that patients with symptomatic PAD reach less than 70% of the distance covered by a healthy individual of the same age. Furthermore, there was a correlation between the relative 6MWT and the DW in all parameters of functional capacity and cardiovascular variables in women. Evidence leads to considering the relativized values of 6MWT and DW as a viable way to assist in the interpretation of 6MWT data.